Comparison of the Picture and Picture Learning Model with the Examples Non-Examples Learning Model on the Learning Outcomes of Students at SMPN 2 Tandukkalua, Mamasa District - Andi Andariana; Ahmad, Fandi (MACCA : Science-Edu Journal, 2024)
This study aims to determine the comparison of learning outcomes of students taught using the Picture and Picture Learning Model with Examples Non-Examples at SMPN 2 Tandukkalua, Mamasa District. This study uses two groups, namely class VIII A with 22 students and class VIII B with 19 students. The variables in this study consist of independent variables, namely the Picture and Picture learning model and Examples Non-Examples, while the dependent variable is learning outcomes. The material taught is the digestive system, and this type of research is quantitative research aimed at determining differences in student learning outcomes. Data collection techniques use tests and documentation. The data analysis techniques used are descriptive analysis and inferential statistical analysis. The results of the study through descriptive analysis show that the learning outcomes of class VIII A students using the Picture and Picture Learning Model (88%) scored between 69.9 and 90.3 with an average of 81, while the learning outcomes of class VIII B students using the Examples Non-Examples Learning Model (70%) scored between 58.2 and 79.6 with an average of 69. The results of the inferential analysis calculation show that the obtained t-value is 2.684 < t-table 3.686 with a significance level of 0.05. Based on these research results, it can be concluded that there is a difference between the two learning models, Picture and Picture, and Examples Non-Examples, on the learning outcomes of eighth-grade students at SMPN 2 Tandukkalua, Mamasa District.